THE RELATIONSHIP BETWEEN ACADEMIC SELF EFFICACIES AND THE ASSERTIVITY ON THE 10 GRADE STUDENTS OF SENIOR HIGH SCHOOL 15 - Vrisca Amelia Suhardi; Sri Hartati; Achmad Mujab Masykur (Jurnal EMPATI, 2013)
Assertivity is important for the teenager in order for them to fulfill their development tasks. Assertivity is the ability of the individual to express their feeling and mind directly, honestly, and clearly while preserving and respecting the rights and feeling of others. As a result of the academic competency that must be fulfilled by the student, consequently the student is demanded to have faith to themselves, it is called self efficacy. The objective of this research is to find out the relationship between academic self efficacy and assetivity on the ten grade students of State Senior High School 15 Semarang.The population of this research are the ten grade students of State Senior High School 15 Semarang. The sampel of this study are 178 students, which is collected through the technique of Cluster Random Sampling. The data collection device in this research is Self Efficacy Scale (34 item α = 0,913) and assertivity scale (33 items α = 0,884) and have been tested to 72 studens of the ten grade on State Senior High School 15 Semarang.The result of the data analysis with the simple regresion analysis generate corelation coeffisien (rxy) 0,512 with p = 0,000 (p<0,05). Those results show the positive relationship which is significan between the academic self efficacy and assertivityon the ten grade students of State Senior High School 15 Semarang. This academic self efficacy give effective contribution as 26,2% on the assertivity of ten grade students of State Senior High School 15 Semarang. The obligation to join the extra curricular has encourage students to actively interact with others. Through the interaction the students can get some experiences result in the increasig self efficacy that lead to the establishment of high assertivity.